Hubungan Gaya Kepemimpinan Tutor Dengan Efektifitas Tutorial Berdasarkan Persepsi Mahasiswa/I Fakultas Kedokteran Universitas Batam Tahun 2016 - Saiful Batubara (BEST Journal (Biology Education, Sains and Technology), 2018)
Tutorial as the necessary main section for medical study process with KBK. The effective tutorial will bring the student to a certain learning condition with high order thinking in a condusive academic climate. To reach the effectiveness of tutorial, some supporting factors is needed such as, trustworthy between the member of the group, scenario or trigger, student participation and interaction, facilities available, also the tutor role. On PBL the tutor role as the facilitator is to ensure the group discussion’s proceed effectively, progressively as well as structurally. Commonly every tutor has it own leadership while proceeding discussion progress that will take effect to student effectiveness on giving opinion. This research is to show the relevance between tutor leadership and tutorial effectivity on student of medical faculty UNIBA academic year 2016. The method for this research is by using observational analytic with cross sectional approach on University Batam Medical Faculy with total sample 184 students and the sampling technique is by simple random sampling. The data analysis is by using Chi-square test. Based on Universitas Batam Medical Faculty student perception, that democratic leadership have a tutorial effectivity by 162 student (88%), authoritarian leadership have a tutorial effectivity by 8 student (4,3%) and freedom leadership have a tutorial effectivity by 11 student (6%). Statistic chi-square test result, show p-value by 0,001 (p 0,05). Based on the research result, it concluded that there is a relevance between tutor leadership and tutorial effectivity based on Universitas Batam Medical Faculty student perception’s